2021
DOI: 10.1111/ijcp.14418
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of women’s pregnancy experiences during the COVID‐19 pandemic: A qualitative study

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic has adversely affected the physical and psychosocial health of pregnant women and their access to antenatal care and health services. Aim To examine women's pregnancy experiences during the COVID‐19 pandemic. Materials and methods The study was conducted in a qualitative design with 14 pregnant women who were admitted to a state hospital pregnancy outpatient clinic for antenatal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
(93 reference statements)
5
31
0
6
Order By: Relevance
“…The same study also revealed that patients preferred private health centres, which they found safer, despite the risk of experiencing economic problems, because of the fear of the virus caused by patient density in the health centres. The studies conducted with pregnant women during the pandemic period emphasised that women preferred hospitals that they found safer due to the cancellation of their appointments at the state hospital and the fear of infection, which is in parallel with our study findings (Aydin & Aktaş, 2021 ; Mizrak Sahin & Kabakci, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…The same study also revealed that patients preferred private health centres, which they found safer, despite the risk of experiencing economic problems, because of the fear of the virus caused by patient density in the health centres. The studies conducted with pregnant women during the pandemic period emphasised that women preferred hospitals that they found safer due to the cancellation of their appointments at the state hospital and the fear of infection, which is in parallel with our study findings (Aydin & Aktaş, 2021 ; Mizrak Sahin & Kabakci, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our participants’ request for more information for groups with comorbidities to help explain their increased risks and what they can do, has been echoed in other studies, including carers of diabetic children and pregnant women. 21 17 22 23 General practitioners across Europe have expressed their concern about ‘collateral damage’ resulting from routine care being postponed or limited due to COVID-19; 24 25 this effect is likely to be greater in ethnic minorities who already have poorer healthcare access. The social isolation and closure of services exacerbated social and mental health problems across all ethnic groups in our study and others, 26 23 but especially effects marginalised and vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of women indicated that they were very anxious about their newborns being infected with COVID-19. In addition, pregnant women expressed concerns about COVID-19 infection and distress about going out during lockdown (Aydin & Aktaş, 2021).…”
Section: Discussionmentioning
confidence: 99%